2015
DOI: 10.3390/rs70506240
|View full text |Cite
|
Sign up to set email alerts
|

Improving Remote Sensing of Aerosol Optical Depth over Land by Polarimetric Measurements at 1640 nm: Airborne Test in North China

Abstract: An improved aerosol retrieval algorithm based on the Advanced Multi-angular Polarized Radiometer (AMPR) is presented to illustrate the utility of additional 1640-nm observations for measuring aerosol optical depth (AOD) over land using look-up table approaches. Spectral neutrality of the polarized surface reflectance over visible to short-wavelength infrared bands is verified, and the 1640-nm measurements corrected for atmospheric effects are used to estimate the polarized surface reflectance at shorter wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Guo et al [33] revealed the spatial and temporal characteristics of AOD values during 1980-2008 over mainland China using the TOMS AOD and MODIS AOD products (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). Meanwhile, many studies on the spatial and temporal variations of AOD values in regional scale in Chinawere conducted using meteorological measurement and satellite signals [10,26,[34][35][36][37][38][39][40]. However, few studies have been made for analyzing the characteristics and driving factors of AOD values in different climate zones and terrain features over mainland China, due to the relative sparse AOD and meteorological measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [33] revealed the spatial and temporal characteristics of AOD values during 1980-2008 over mainland China using the TOMS AOD and MODIS AOD products (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). Meanwhile, many studies on the spatial and temporal variations of AOD values in regional scale in Chinawere conducted using meteorological measurement and satellite signals [10,26,[34][35][36][37][38][39][40]. However, few studies have been made for analyzing the characteristics and driving factors of AOD values in different climate zones and terrain features over mainland China, due to the relative sparse AOD and meteorological measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the first scenario (P1), we consider only the polarized radiances Q and U at 490, 670, and 870 nm corresponding to the POLDER/Polarization and Anisotropy of Reflectances for Atmospheric Science coupled with Observations from a Lidar instrument (Deuzé et al, , ), and the 490 nm band is used instead of 443 nm (Tanré et al, ). Polarimetric measurements at 1,610 nm are added to the second scenario (P2) to represent the airborne Advanced Atmosphere Multiangle Polarization Radiometer instrument (Qie et al, ). Next, the third scenario (P3) is defined identical to scenario P2 in addition to polarimetric measurements at 2,250 nm to represent the MICROPOL instrument (Goloub et al, ; Waquet et al, ; Waquet, Cairns, et al, ).…”
Section: Model and Methodologymentioning
confidence: 99%
“…Recently, another new spaceborne instrument known as the Polarized Scanning Atmospheric Corrector (PSAC), which was designed with multispectral single‐viewing polarimetric measurements, was also developed in China to provide aerosol properties for the atmospheric corrections of other sensors onboard the same satellite. The airborne prototype of PSAC, namely, the Advanced Atmosphere Multiangle Polarization Radiometer, has been employed for some aerosol retrieval tests (Hou et al, ; Qie et al, ; Wang, Sun, et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The spectral sensitivities of the polarized reflectances obtained from research scanning polarimeter and micropolarimeter measurements over vegetated surfaces were studied previously Waquet, Léon, et al, 2009), and the offsets of the regression lines were determined as small with slopes close to 1. This conclusion has been applied to aerosol retrieval for a number of airborne polarimetric instruments, such as the research scanning polarimeter and the advanced multi-angle polarization radiometer (Qie et al, 2015;Wang et al, 2014Wang et al, , 2017). This conclusion has been applied to aerosol retrieval for a number of airborne polarimetric instruments, such as the research scanning polarimeter and the advanced multi-angle polarization radiometer (Qie et al, 2015;Wang et al, 2014Wang et al, , 2017).…”
Section: Introductionmentioning
confidence: 99%